2013
DOI: 10.1109/lsp.2013.2274774
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Estimation of a Gaussian Source in Middleton's Class-A Impulsive Noise

Abstract: The paper focuses on minimum mean square error (MMSE) Bayesian estimation for a Gaussian source impaired by additive Middleton's Class-A impulsive noise. In addition to the optimal Bayesian estimator, the paper considers also the soft-limiter and the blanker, which are two popular suboptimal estimators characterized by very low complexity. The MMSE-optimum thresholds for such suboptimal estimators are obtained by practical iterative algorithms with fast convergence. The paper derives also the optimal threshold… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…In addition, power allocation algorithms can be exploited without changing the DVB-T receiver. Another possibility is the investigation of the effect of impulsive noise [34], non-Gaussian channels, and quantization errors [35], on the DVB-T received signal. Furthermore, by means of our SDR-based design, the DVB-T signal can first be received by a custom DVB-T receiver and then retransmitted to a single destination by a regenerative relay, nearby to the receiver.…”
Section: Impactmentioning
confidence: 99%
“…In addition, power allocation algorithms can be exploited without changing the DVB-T receiver. Another possibility is the investigation of the effect of impulsive noise [34], non-Gaussian channels, and quantization errors [35], on the DVB-T received signal. Furthermore, by means of our SDR-based design, the DVB-T signal can first be received by a custom DVB-T receiver and then retransmitted to a single destination by a regenerative relay, nearby to the receiver.…”
Section: Impactmentioning
confidence: 99%
“…Proof: Using the Sherman-Morrison formula [17], (32) becomes [15] that is different from the MSNR solution [16]. Therefore, the equivalence between MMSE and MSNR estimators can be invalid for non-BEM-based suboptimal estimators.…”
Section: B B-mmse Estimatormentioning
confidence: 99%
“…However, the performance of estimation techniques in the presence of impulsive noise is not widely acknowledged. Recently, the authors in [9] considered the MMSE optimal Bayesian estimation (OBE) for a Gaussian source impaired by Middleton class-A impulsive noise. It is shown that the performance of the proposed MMSE OBE strictly depends on the statistical characteristics of the received signal.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results showed that the performance improvement of the optimal MMSE estimator over the linear MMSE (LMMSE) estimator under this condition is substantial. However, the analyses in [9], [10] are restricted to the point-to-point scenario and the effect of channel fading is not considered. To the best of authors knowledge, no result exists for the distributed estimation of Gaussian sources in the presence of impulsive noise under Rayleigh fading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation